EVALUASI STRATEGI KEPALA PERPUSTAKAAN SEKOLAH DALAM MENINGKATKAN MINAT BACA SISWA DI SMPN 6 KARAWANG BARAT - Amelia, Cindy; Permana, Hinggil; Mustofa, Taufik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the strategies of the school library head in increasing students' reading interest at SMPN 6 Karawang Barat. This study uses a descriptive qualitative approach with descriptive methods. Data collection techniques include observation, interviews, and documentation with key informants, namely the head of the school library, librarians, and students. Data analysis is conducted through data reduction, data presentation, and drawing conclusions. The results of this study indicate that strategy formulation is carried out systematically through coordination meetings involving the library head and librarians. The implementation of strategies includes monthly joint reading activities held in the schoolyard, literacy tree programs in each class, reading corners, and literacy competitions. Strategy evaluation is conducted routinely on a monthly, semester, and annual basis using indicators such as the number of visits, book borrowing, observations, and coordination meetings. The evaluation results showed an increase in students' reading interest, although it is not yet optimal. In conclusion, the library head's strategy has been running quite well but still requires improvements in the addition of book collections and facilities.